Caloric Intake, Dietary Lifestyles, Macronutrient Composition, and Alzheimer' Disease Dementia. (26th July 2011) - Pasinetti, Giulio Maria; Wang, Jun; Porter, Shanee; Ho, Lap
Abstract : Alzheimer's disease is a devastating neurodegenerative condition currently affecting over 5 million elderly individuals in the United States. There is much evidence suggesting that certain dietary lifestyles can help to prevent and possibly treat Alzheimer's disease. In this paper, we discuss how certain cardiovascular and diabetic conditions can induce an increased susceptibility for Alzheimer's disease and the mechanisms through which this occurs. We further discuss how the consumption of certain foods or food components can help to reduce one's risk for Alzheimer's disease and may possibly be developed as a therapeutic agent.